Rushing to judgment and the banking crisis of 2023 - Steven Kelly; Jonathan Rose (Federal Reserve Bank of Chicago, 2025)
This article critically reviews the 2023 banking crisis with the benefit of two years of hindsight. We highlight seven facts that depart from the standard account of the crisis that has developed. We describe the crisis as a reaction to bank business models that focused on providing banking services to certain economic sectors, crypto-asset firms and venture capital, that had come under economic pressure during the preceding year. We argue this view of the crisis provides a more precise explanation of which banks were affected compared to an explanation focused solely on banks' balance sheet metrics. We also argue that this view of the crisis has different policy implications, more focused on surveilling bank business models and institutional depositors.
Keywords: G01; G21; G28; H12; 330; Banking Crisis of 2023; business model risk; Silicon Valley Bank; uninsured deposits; unrealized losses